37.3k views
3 votes
How to solve this

6m+6+7(1-3m)=-32​

User Mishac
by
5.0k points

2 Answers

0 votes

Answer:

m = 3

Explanation:

6m + 6 + 7(1 - 3m) = -32 (distruibute)

6m + 6 + 7 - 21m = -32 (collect like terms)

-15m + 13 = -32 ( subtract 13 on both sides to get rid of it on the left side)

-15m = -45 (divide by -15 on both sides to get m alone)

m = 3

HOPE THIS HeLPeD!!

User Shakia
by
5.5k points
0 votes

Answer:

m=15

Explanation:

BODMAS

6m+6+7-3m=-32

collect like terms

6m-3m+6+7=-32

3m+13=-32

3m=-32-13

3m=45

m=45/3

m=15

User Vikrant Rana
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.